Electro-Hydrodynamic Drop-on-Demand Printing of Aqueous Suspensions of Drug Nanoparticles - Ezinwa Elele; Yueyang Shen; Rajyalakshmi Boppana; Afolawemi Afolabi; Ecevit Bilgili; Boris Khusid (MDPI AG, 2020)
We demonstrate the ability to fabricate dosage forms of a poorly water-soluble drug by using wet stirred media milling of a drug powder to produce an aqueous suspension of nanoparticles and then print it onto a porous biocompatible film. Contrary to conventional printing technologies, a deposited material is pulled out from the nozzle. This feature enables printing highly viscous materials with a precise control over the printed volume. Drug (griseofulvin) nanosuspensions prepared by wet media milling were printed onto porous hydroxypropyl methylcellulose films prepared by freeze-drying. The drug particles retained crystallinity and polymorphic form in the course of milling and printing. The versatility of this technique was demonstrated by printing the same amount of nanoparticles onto a film with droplets of different sizes. The mean drug content (0.19-3.80 mg) in the printed films was predicted by the number of droplets (5-100) and droplet volume (0.2-1.0 µL) (R2 = 0.9994, p-value < 10−4). Our results also suggest that for any targeted drug content, the number-volume of droplets could be modulated to achieve acceptable drug content uniformity. Analysis of the model-independent difference and similarity factors showed consistency of drug release profiles from films with a printed suspension. Zero-order kinetics described the griseofulvin release rate from 1.8% up to 82%. Overall, this study has successfully demonstrated that the electro-hydrodynamic drop-on-demand printing of an aqueous drug nanosuspension enables accurate and controllable drug dosing in porous polymer films, which exhibited acceptable content uniformity and reproducible drug release.